A highly N-doped carbon phase "dressing" of macroscopic supports for catalytic applications1. Issue 76 (10th October 2015) - Ba, Housseinou; Liu, Yuefeng; Truong-Phuoc, Lai; Duong-Viet, Cuong; Mu, Xiaoke; Doh, Won Hui; Tran-Thanh, Tung; Baaziz, Walid; Nguyen-Dinh, Lam; Nhut, Jean-Mario; Janowska, Izabela; Begin, Dominique; et al.
<x xml:space="preserve">Abstract</x> Various macroscopic and porous host scaffolds are easily "dressed" with highly N-doped carbon-based coatings. The as prepared composites act as effective metal-free catalysts in industrial key-processes.